2017
DOI: 10.1186/s12879-017-2536-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous catheter-related bloodstream infection is associated with severe complications and potential death: a retrospective observational study

Abstract: BackgroundThe purpose of this study was to identify the clinical characteristics and outcomes of peripheral vascular catheter-related bloodstream infections (PVC-BSIs) and determine the risk of severe complications or death.MethodsWe performed a retrospective observational study from June 2010 to April 2015 at two regional university-affiliated hospitals in Tokyo. We studied the clinical manifestations, underlying diseases, laboratory results, treatment methods, recurrence rates, and complications in 62 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 22 publications
5
72
1
8
Order By: Relevance
“…The reported frequency of PVC-related bloodstream infections was quite low, ranging from 0.08 to 6.9% for local infections and 0.036 to 0.1% for severe systemic infections, respectively [9,10]. However, once these infections present, they are associated with high morbid- ity and mortality [11]. Even though the incidence rate of thrombophlebitis is 6.8-21.7%, we did not observe this complication in our study period [12,13].…”
Section: Discussioncontrasting
confidence: 46%
“…The reported frequency of PVC-related bloodstream infections was quite low, ranging from 0.08 to 6.9% for local infections and 0.036 to 0.1% for severe systemic infections, respectively [9,10]. However, once these infections present, they are associated with high morbid- ity and mortality [11]. Even though the incidence rate of thrombophlebitis is 6.8-21.7%, we did not observe this complication in our study period [12,13].…”
Section: Discussioncontrasting
confidence: 46%
“…Current clinical practice guidelines (8) do not specifically refer to PVC tip culture and suggest systematic removal and culture of the catheter in case of suspected intravascular catheter-related bloodstream infection. Moreover, data regarding the proportion of PVC tip cultures performed in patients with suspected PVCRBSI are scarce, and when reported the proportion is frequently under 50% (18,19). Given these findings, we may conclude that a systematic removal and culture of PVC should be performed not only in all patients with clinical apparent phlebitis but also in subjects with systemic signs of infection and without a known septic focus.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, patients who remain on PVC for longer than the routine indwelling time might be more susceptible to infection. To our knowledge, although the incidence of infection is very low, the literature indicates that once the infection occurs, the patient's hospital stay will be prolonged, and mortality can even occur (Guembe et al, ; Sato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that increased dwell time may increase the risk of PVC failure in adult patients (Cicolini, Manzoli, et al, 2014a;Mermel, 2017;Sato et al, 2017), while some studies have also indicated there was no association between catheter dwell time and phlebitis (Braga et al, 2018), and catheter-related infections (Guembe et al, 2017). These inconsistent findings may be related to various confounding factors.…”
Section: Introductionmentioning
confidence: 99%